2004
DOI: 10.1002/ana.20094
|View full text |Cite
|
Sign up to set email alerts
|

SIMPLE mutation in demyelinating neuropathy and distribution in sciatic nerve

Abstract: Charcot-Marie-Tooth neuropathy type 1C (CMT1C) is an autosomal dominant demyelinating peripheral neuropathy caused by missense mutations in the small integral membrane protein of lysosome/late endosome (SIMPLE) gene. To investigate the prevalence of SIMPLE mutations, we screened a cohort of 152 probands with various types of demyelinating or axonal and pure motor or sensory inherited neuropathies. SIMPLE mutations were found only in CMT1 patients, including one G112S and one W116G missense mutations. A novel I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 27 publications
2
53
0
3
Order By: Relevance
“…The Gly112Ser mutation in the LITAF gene detected in the CMT family may act in our patient at least in two independent ways. In the peripheral nerve, the mutated LITAF gene causes a typical course of mild peripheral demyelinating neuropathy seen in our proband's affected family members, and was previously described in other CMT1C patients harbouring Gly112Ser mutation [1,8,16,18].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The Gly112Ser mutation in the LITAF gene detected in the CMT family may act in our patient at least in two independent ways. In the peripheral nerve, the mutated LITAF gene causes a typical course of mild peripheral demyelinating neuropathy seen in our proband's affected family members, and was previously described in other CMT1C patients harbouring Gly112Ser mutation [1,8,16,18].…”
Section: Discussionsupporting
confidence: 72%
“…CMT1C disease is caused by mutations in the lipopolysaccharide-induced tumor necrosis factor-α (LITAF) gene on chromosome 16p12-16p13.3 [1,18,19]. To date only nine pathogenic mutations in the LITAF gene have been reported [6].…”
Section: Introductionmentioning
confidence: 99%
“…Genetic studies have identified eight missense mutations in small integral membrane protein of lysosome/late endosome (SIMPLE) that cause autosomal dominant, demyelinating CMT type 1C (CMT1C) (Street et al, 2003;Bennett et al, 2004;Saifi et al, 2005;Latour et al, 2006;Gerding et al, 2009). SIMPLE, also known as lipopolysaccharide-induced TNF-a factor (LITAF), is a 161 amino acid protein that has been implicated in cytokine signaling (Moriwaki et al, 2001;Bolcato-Bellemin et al, 2004) and tumor suppression (Mestre-Escorihuela et al, Wang et al, 2009), but its precise cellular function remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…SIMPLE is also clinically important in that specific point mutations in one of the alleles causes autosomal-dominant Charcot-Marie-Tooth type 1C (CMT1C) demyelination (25)(26)(27)(28)(29). To better character CMT1C pathogenesis, we generated a physiological knock-in mouse model with one mutated SIMPLE allele (Simple T115N/ϩ ) (24 (24).…”
mentioning
confidence: 99%